A new Argentinean nesting site showing neosauropod dinosaur reproduction in a Cretaceous hydrothermal environment - Grellet-tinner, Gerald (2010)
Although several late Cretaceous sauropod colonial nesting sites have been discovered nearly on every continent during the last few decades, no studies have been performed to determine the factors that underpinned the choice of these specific sites. Here, we report the first definitive evidence of a group of sauropods that nested repetitively and purposely at a Cretaceous hydrothermal site at Sanagasta, La Rioja Province, Argentina. The discovery of this new colonial nesting locality shows nest fidelity over a long time, and a symbiotic relationship between egg clutches and a peculiar hydrothermal environment that favoured their incubation. Sedimentary and geochemical analyses of 80 clutches and their large eggs with thick eggshells substantiate that the Sanagasta sauropods were specifically using the soil moisture and thermoradiance to incubate their eggs, similar to a few extant species, namely, the megapode, Megapodius pritchardii, which is known to lay its egg clutches in burrows at volcanically heated nesting grounds.